Drivers of the Smart Green Economy in Rural Settings: An Empirical Study on Local Wisdom, ICT, and the Mediating Role of Entrepreneurship - ANDRIA, Fredi; TOSIDA, Eneng Tita; JAYAWINANGUN, Roni; SAPUTRA, Jumadil (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025DO - 10.14505/tpref.v16.3(35).10, 2025)
This study provides local governments with critical insights into the role of Micro, Small, and Medium Enterprises (MSMEs) in advancing smart green economies within smart villages, particularly through the lenses of local wisdom, Information and Communication Technology (ICT), and entrepreneurship. Drawing on a sample of 142 MSME participants, the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among key variables. Findings reveal that the interplay between local economic practices, ICT adoption, and entrepreneurial capacity significantly influences the development of a smart green economy. Notably, integrating indigenous knowledge with digital technologies emerges as a pivotal driver of economic transformation. Local wisdom and knowledge shape products and services' unique character and cultural value, helping communities stand out and grow their economies. When people in these communities use digital tools, especially the internet, in their businesses, it opens up new opportunities and encourages innovation. Still, having strong entrepreneurial skills is key. They do not directly drive the economy, but they help connect traditional wisdom and modern technology in ways that make growth possible. It demonstrates the importance of blending traditional heritage with innovation to create a thriving, sustainable future for rural areas.